INFLUENCE OF WORK DISCIPLINE, WORK MOTIVATION AND COMPENSATION TO PERFORMANCE TEACHER IN TOJO DISTRICT, TOJO UNA-UNA DISTRICT - Ulfa Reniyanti; I Nengah Suarmanayasa; Ni Nyoman Yulianthini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Study This aim For prove in a way empirical influence discipline work motivation, and compensation on teacher performance in Tojo District, Tojo Una-Una Regency. This study uses a quantitative approach. The population in study This is Teacher SENIOR HIGH SCHOOL in Subdistrict Tojo Regency Tojo Una-Una. Technique taking sample use technique census (sample saturated), so that all members of the population are used as research samples. Data collection was conducted using a questionnaire compiled on a Likert scale with a rating range of 1–5. The data obtained were analyzed using multiple linear regression analysis with the help of the IBM SPSS program. The results of the study indicate that work discipline, work motivation, and compensation partially have a positive and significant effect on teacher performance. Furthermore, these three independent variables simultaneously significantly influence teacher performance in Tojo District, Tojo Una-Una Regency. The findings of this study indicate that improving teacher performance can be achieved through strengthening work discipline, increasing work motivation, and providing fair and appropriate compensation .